A revised checklist of Odonata (Insecta) from Marambaia, Rio de Janeiro, Brazil with eight new records - Anjos-Santos, Danielle; Costa, Janira M. (Zootaxa, 2006)
A list of 77 species in 37 genera and 10 families recorded in Marambaia, Rio de Janeiro, Brazil is presented. Eight species (Hetaerina brigthwelli (Kirby); Lestes tricolor Erichson; Ischnura fluviatilis Selys; Leptagrion andromache Hagen in Selys; Triacanthagyna nympha (Navás); Triacanthagyna septima (Selys in Sagra); Zonophora campanulata campanulata (Burmeister) and Micrathyria borgmeieri Santos) have been recorded for the first time for the region, enlarging the knowledge about Odonata species of Rio de Janeiro State. Comments about new records and additional relevant literature are discussed.